2001
DOI: 10.2337/diabetes.50.2.392
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-Term Improvement of Insulin Treatment and Glycemia on Hepatic Glycogen Metabolism in Type 1 Diabetes

Abstract: Insufficiently treated type 1 diabetic patients exhibit inappropriate postprandial hyperglycemia and reduction in liver glycogen stores. To examine the effect of acute improvement of metabolic control on hepatic glycogen metabolism, lean young type 1 diabetic (HbA 1c 8.8 ± 0.3%) and matched nondiabetic subjects (HbA 1c 5.4 ± 0.1%) were studied during the course of a day with three isocaloric mixed meals. Hepatic glycogen concentrations were determined noninvasively using in vivo 13 C nuclear magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
80
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 60 publications
9
80
1
2
Order By: Relevance
“…We cannot exclude the possibility that the association between lipid oxidation and IHF content would have been stronger if more specific measures had been employed. The finding of depleted liver fat content in patients with type 1 diabetes is remarkably similar to the finding of depleted liver glycogen stores in patients with similar features [27,28]. In this regard, we need to emphasise that in the present study the patients were studied as they were in their everyday life (poor metabolic control), and therefore it is likely that these findings do not represent an intrinsic alteration but rather that they may be due to the poor therapeutic control.…”
Section: Discussionsupporting
confidence: 65%
“…We cannot exclude the possibility that the association between lipid oxidation and IHF content would have been stronger if more specific measures had been employed. The finding of depleted liver fat content in patients with type 1 diabetes is remarkably similar to the finding of depleted liver glycogen stores in patients with similar features [27,28]. In this regard, we need to emphasise that in the present study the patients were studied as they were in their everyday life (poor metabolic control), and therefore it is likely that these findings do not represent an intrinsic alteration but rather that they may be due to the poor therapeutic control.…”
Section: Discussionsupporting
confidence: 65%
“…Both defects in glycogen metabolism were improved, but not normalized, by short-term restoration of insulinemia and glycemia through intensified insulin treatment for 24 hours [98]. However, a subsequent study by the same researchers found that strict long-and short-term metabolic control using peripheral insulin substitution normalized hepatic glycogen synthesis, hepatic glycogenolysis, and nocturnal endogenous glucose production fasting in type 1 diabetic subjects.…”
Section: Glycogen Synthesis and Breakdown In Type 1 Diabetesmentioning
confidence: 90%
“…During all protocols, liver glycogen concentrations were measured from −40 to −10 min, 10 to 40 min, 120 to 150 min, and from 300 to 360 min on a 3.0-T/80-cm bore NMR spectrometer (Medspec, Bruker, Ettlingen, Germany). Localized 13 C resonance spectra were obtained with a 10 cm circular 13 C/ 1 H transmitter/receiver coil placed rigidly over the lateral aspect of the liver by applying a modified onedimensional inversion-based sequence [18,20,26]. Typically, one spectrum consists of 5000 scans and requires 15 min of signal averaging.…”
Section: Methodsmentioning
confidence: 99%